A phloem-specific sucrose-H+ symporter from Plantago major L. supports the model of apoplastic phloem loading. - Gahrtz, Manfred; Stolz, Jürgen; Sauer, Norbert (Plant Journal, 1994)
In this paper the cloning of a full-length cDNA clone encoding the PmSUC2 sucrose-H+ symporter from Plantago major is described. This plant allows the simple preparation of vascular bundles from the basal regions of fully developed source leaves and thus a separation of vascular and non-vascular tissue. A cDNA library was constructed from poly(A)+ RNA isolated from vascular bundles and used for the subsequent cloning of cDNAs. The respective mRNA is specifically expressed in the vascular bundles as shown on Northern blots of total RNA from vascular and non-vascular tissues. The PmSUC2 protein has 12 putative transmembrane helices and is highly homologous to other plant sucrose transporters. Substrate specificity and energy dependence of the transporter encoded by this cDNA were determined by expression in baker's yeast Saccharomyces cerevisiae. The PmSUC2 protein catalyses the transport of sucrose into transgenic yeast cells. Invertase null mutants of yeast expressing PmSUC2 accumulate sucrose more than 200-fold. This transport was sensitive to uncouplers or SH-group inhibitors. Plasma membranes from yeast cells expressing the PmSUC2 protein were purified and fused to proteoliposomes containing cytochrome-c-oxidase. In this system sucrose is accumulated only when proton motive force is generated, indicating that PmSUC2 is a sucrose-H+ symporter. The apparent molecular weight of the PmSUC2 protein is 35 kDa on 10% SDS-polyacrylamide gels. The presented data strongly support the theory of phloem loading from the apoplastic space by a sucrose-H+ symporter.